Effects of Glycemic Control upon Serum Lipids and Lipid Transfers to HDL in Patients with Type 2 Diabetes Mellitus: Novel Findings in Unesterified Cholesterol Status - Laverdy, O. G.; Hueb, W. A.; Sprandel, M.C. O.; Kalil-Filho, R.; Maranhão, R. C. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Objective: Investigate the relations of glycemic levels with plasma lipids and in vitro lipid transfers to HDL in patients with type 2 diabetes mellitus.Materials and Methods: 143 patients with type 2 diabetes not taking anti-lipidemic drugs were separated into 2 groups: group A included 62 patients with glycated hemoglobin (HbA1c)≤6.5% (48 mmol/mol) and group B 81 patients with HbA1c>6.5%. In vitro transfer of lipids was determined by 1 h incubation of a donor nanoemulsion containing radioactively labeled unesterified and esterified cholesterol, phospholipids and triglycerides with whole plasma followed by chemical precipitation and radioactive counting in the supernatant (HDL).Results: LDL and HDL cholesterol were similar in Group A and B, but group B had higher triglycerides (2.31±1.30 vs. 1.58±0.61 mmol/l, P<0.0001) and total and non-HDL unesterified cholesterol (36.3±7.8 vs. 33.9±5.9 mmol/l, P<0,05; 30.6±7.9 vs. 27.6±6.2 mmol/l, P<0,05; respectively) than group A and a non-significant trend to increased apolipoprotein B (103±20 vs. 97±20 mg/dl, P=0.08). 36 patients with the highest, ≥8.0% (64 mmol/mol), HbA1c also showed non-significant trend of elevated non-esterified fatty acids (NEFA) compared to 37 with lowest, ≤6.0% (42 mmol/mol), HbA1c (P=0.08). Patients with higher NEFA had higher triglycerides than those with lower NEFA levels (P<0.01).Transfers of all lipids from nanoemulsion to HDL and lipid composition of HDL were equal in both groups.Conclusions: For the first time it was shown that in addition to triglycerides, unesterified cholesterol is also a marker of poor glycemic control. In vitro HDL lipid transfers, an important aspect of HDL metabolism, were not related with the glycemic control.
Keywords: glycated hemoglobin; diabetic dyslipidemia; lipoproteins metabolism